2018
DOI: 10.18632/oncotarget.23882
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the number of mutations in survival and response outcomes to hypomethylating agents in patients with myelodysplastic syndromes or myelodysplastic/myeloproliferative neoplasms

Abstract: The prognostic and predictive value of sequencing analysis in myelodysplastic syndromes (MDS) has not been fully integrated into clinical practice. We performed whole exome sequencing (WES) of bone marrow samples from 83 patients with MDS and 31 with MDS/MPN identifying 218 driver mutations in 31 genes in 98 (86%) patients. A total of 65 (57%) patients received therapy with hypomethylating agents. By univariate analysis, mutations in BCOR, STAG2, TP53 and SF3B1 significantly influenced survival. Increased numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 42 publications
3
27
2
2
Order By: Relevance
“…Somatic mutation status may, however, predict duration of response to therapy. Mutations in DNA methylation regulators and the presence of 3 or more mutations have been associated with a shorter duration of response to DNMTIs (Montalban‐Bravo et al , ). Recent retrospective data suggests that the duration of response to DNMTIs is significantly shorter in patients with TP53 mutations, roughly 6 months versus 29 months, although this study did not detect a difference in overall response rate based on TP53 mutational status (Takahashi et al , ).…”
Section: Ngs Results and Treatment Implicationsmentioning
confidence: 99%
“…Somatic mutation status may, however, predict duration of response to therapy. Mutations in DNA methylation regulators and the presence of 3 or more mutations have been associated with a shorter duration of response to DNMTIs (Montalban‐Bravo et al , ). Recent retrospective data suggests that the duration of response to DNMTIs is significantly shorter in patients with TP53 mutations, roughly 6 months versus 29 months, although this study did not detect a difference in overall response rate based on TP53 mutational status (Takahashi et al , ).…”
Section: Ngs Results and Treatment Implicationsmentioning
confidence: 99%
“…From the available data, it is known that the presence of a number of somatic mutations can affect the response rates to therapy and the level of overall survival [12]. Mutations in the TET2, DNMT3A, TP53 genes were reported to be associated with a high probability of response to HMA [13,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…5 DNMT3A and TP53 mutations, although less common in CMML, have also been associated with poorer OS. 6,7 It is noteworthy that the number of mutations also influences patients' outcomes, as recently demonstrated in a study in which a shorter OS was observed in CMML patients with three or more concomitant mutations. 7 Specific prognostic scoring systems for individual risk assessment are essential in order to provide risk-adapted treatment.…”
mentioning
confidence: 88%
“…6,7 It is noteworthy that the number of mutations also influences patients' outcomes, as recently demonstrated in a study in which a shorter OS was observed in CMML patients with three or more concomitant mutations. 7 Specific prognostic scoring systems for individual risk assessment are essential in order to provide risk-adapted treatment. The most commonly used are the CMML-specific prognostic scoring system (CPSS), 8 the MD Anderson Cancer Center prognostic score (MDAPS) 9 and the revised International Prognostic Scoring System (IPSS-R) 10 (the last only being applicable to "dysplastic" CMML).…”
mentioning
confidence: 88%